Impact Of Vijay Neem On Histological And Scanning Electron Microscopic Changes In The Testis Of Adult Male Insect Odontopus Vericornis (Dist) (Heteroptera: Pyrrchocoridae) - AMBIKA; Mrs.SELVISABHANAYAKAM (International Journal of Pharma and Bio Sciences, 2012)
Pesticides are one of the major xenobiotic substances that have been used in India. Pesticides pollution in terrestrial environment produce sudden and drastic changes in all living organisms. Synthetically produced organic insecticides are the principal means of managing insect pests. Their use however is associated with some major problems such as long term persistence, highly toxic to non-target organisms, bioaccumulation, environmental contamination and their over increasing coast. Therefore, there is the search for sound and safe method for managing insect pest by using phytopesticide on very serious pest, Odontopus vericornis. Keeping in this view, the present study is aimed to find out the histological and scanning electron microscope changes in the testis of adult male Odontopus vericornis treated with the sub- lethal concentration (LD50 3.5%) of vijay neem for 48 h. The present results revealed that characteristic histological changes in the testis of treated insect than the control insect such as apical cells lost their shape and size, scattered with intracellular spaces, scanty cytoplasm, hypertrophy, intensive reaction with eosin, testis follicle showed necrosis, breakage of spertomatozoa and spermatids. Scanning electron microscopic changes are observed such as myoepithelial cells highly necrotic and pycnotic, testis follicle are comparatively shrunken than control insect. Secretary granules became disintegrated and disorganized.